Peran Kiai dalam Pemilihan Bupati dan Wakil Bupati Kabupaten Blitar Tahun 2020 - Andi Prasetiyo; Meidi Kosandi (Jurnal Syntax Admiration, 2024)
This study examines the role of Kiai in the 2020 Blitar Regency Regent and Deputy Regent Election, especially in supporting the incumbent candidate pair. The main focus is to understand how Kiai, as part of a non-party social network, captures voter support and why they failed to win over the incumbent candidate's pair. This study also explores the motivation of Kiai in providing support and the form of patron-client relationship between Kiai and students or the voting community. Through qualitative descriptive methods, this study reveals that although the support of Kiai and ulama is important, the personal charisma of the candidates and the limitations of the campaign due to the Covid-19 pandemic also greatly affect the election results. The results of this study are expected to provide insight into local political dynamics and the important role of Kiai in political contestation in Blitar Regency.